lac Thiogalactoside transacetylase of Escherichia coli K-12 and ML. - Fried, V A (1980)
The lac thiogalactoside transacetylase was purified from both a wild-type Escherichia coli K-12 strain (H3000) and an E. coli ML strain (ML308). These enzymes are indistinguishable by using several criteria. The subunit molecular weight of the enzyme is 24,800, which is significantly less than the previously reported value of 30,000. Although the function of the thiogalactoside transacetylase is unknown, it is suggested that this enzyme plays an important role in lactose utilization since its structure and enzymatic activity have been conserved.